2022
DOI: 10.1155/2022/4558782
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Prognosis and Molecular Mechanism of Ferroptosis in Hepatocellular Carcinoma Based on Bioinformatics Methods

Abstract: Background. As an iron-dependent type of programmed cell death, ferroptosis plays an important role in the pathogenesis and progression of hepatocellular carcinoma (HCC). Long noncoding RNAs (lncRNAs) have been linked to the prognosis of patients with HCC in a number of studies. Nevertheless, the predictive value of lncRNAs (FRLs) associated with ferroptosis in HCC has not been fully elucidated. Methods. Download RNA sequencing data and clinical profiles of HCC patients from The Cancer Genome Atlas (TCGA) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recently, signature models using lncRNAs and ferroptosis were established, classifying HCC patients into two groups. The high-risk group had enhanced hepatocarcinogenesis and poor prognosis [ 467 , 468 ]. Equally, non-coding circular RNAs (circRNAs) are associated with the development of HCC through ferroptosis.…”
Section: Interplay Between Apoptosis and Autophagymentioning
confidence: 99%
“…Recently, signature models using lncRNAs and ferroptosis were established, classifying HCC patients into two groups. The high-risk group had enhanced hepatocarcinogenesis and poor prognosis [ 467 , 468 ]. Equally, non-coding circular RNAs (circRNAs) are associated with the development of HCC through ferroptosis.…”
Section: Interplay Between Apoptosis and Autophagymentioning
confidence: 99%
“… Wan et al (2022) screen 5 ferroptosis-related markers [G6PD, HMOX1 (heme oxygenase 1), LOX (lysyl oxidase), SLC7A11, and STMN1 (stathmin 1)], which are associated with higher tumor-node-metastasis stage, cirrhosis and immunosuppressive microenvironment in tumor tissue, and further well predict the prognosis of HCC. Studies have found that ferroptosis-related genes serve as independent risk factors to evaluate the clinical efficacy of chemotherapy and immunotherapy in HCC ( Gao R. et al, 2021 ; Xiong et al, 2022 ). The establishment of markers associated with ferroptosis will be beneficial to predict the biological characteristics of HCC and select the optimal therapeutics for HCC patients.…”
Section: Ferroptosis In Hccmentioning
confidence: 99%
“…Further analysis revealed that these prognostic models may regulate HCC immune microenvironment via modulating immune-related pathways, such as the TNF-α/NF-κB and IL-2/STAT5 signaling pathways, which further affects the differentiation of immune infiltration ( Xu Z. et al, 2021 ; Yang X. et al, 2022 ). There are other prediction models showing ferroptosis-related lncRNAs associated with immunity, tumor microenvironment alteration, chemotherapeutic, and immunotherapeutic efficacy in HCC ( Fang et al, 2022 ; Xiong et al, 2022 ). Besides, 17 ferroptosis-associated lncRNAs are identified as a prognostic and risk model for accurate decision making in clinical treatment and immunotherapy of HCC ( Lin and Yang, 2022 ).…”
Section: Ferroptosis-related Ncrnas In Hccmentioning
confidence: 99%
“…Liver cancer is among the highest prevalent existing malignancy, leading to approximately 662,000 deaths each year, and its prevalence and death rates are rising year by year globally [ 1 , 2 ]. As the primary histological sub kind of liver cancer, hepatocellular carcinoma (HCC) denotes about 75% of all instances [ 3 ]. Currently, HCC is typically treated with liver resection, liver transplantation, thermal ablation, trans-arterial chemoembolization (TACE), hepatic arterial infusion chemotherapy (HAIC), personalized treatment, and immunotherapy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%